Effect of Maternal Obstetrical Factors on Birth Weight of New Born - et. al, Mrs. Nitanjali Vaibhav Patil (International Journal of Advanced Science and Technology, 2020)
Abstract- Pregnancy is a characteristic occasion in conceptive age ladies; it's a period of joy for the eager mother, regularly it is presented as an energizing time. Study was conducted to assess the effect of the maternal obstetrical factors on birth weight of new born and to find an association between maternal obstetrical factors with birth weight of new born. Methods The investigation convention was checked on and endorsed by the Ethics Committee .We confined our study to patients who conveyed a solitary live newborn child somewhere in the range of 37 and 41 weeks of growth and avoided those for whom information were inaccessible. Data analysis-The data were analyzed utilizing the SPSS20 version. Results- the  maternal obstetrical factors like gravid, para, number of abortions, stillbirths,  number of deaths and number of live births were  not significantly associated with birth weight of new born as p value was >0.05. Proportion of LBW was significantly higher in women whose present pregnancy was unplanned indicates unplanned pregnancy was significantly associated with birth weight of new born p value =0.0067, History of infertility revealed high proportion LBW indicates women with history of infertility was significantly associated with birth weight of new born p value= <0.0197 anemia during pregnancy was significantly associated with birth weight of new born p value= <0.0043. Conclusions-Maternal obstetrical factors were significantly associated with birth weight of new born with interval between two deliveries, history of infertility, unplanned pregnancy history of consanguineous marriage and hemoglobin percentage of mother. In the present study there was significantly high proportion of female babies were with LBW as compared to male babies